2014
DOI: 10.1016/j.joca.2014.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Rapid, automated imaging of mouse articular cartilage by microCT for early detection of osteoarthritis and finite element modelling of joint mechanics

Abstract: SummaryObjectiveMouse articular cartilage (AC) is mostly assessed by histopathology and its mechanics is poorly characterised. In this study: (1) we developed non-destructive imaging for quantitative assessment of AC morphology and (2) evaluated the mechanical implications of AC structural changes.MethodsKnee joints obtained from naïve mice and from mice with osteoarthritis (OA) induced by destabilization of medial meniscus (DMM) for 4 and 12 weeks, were imaged by phosphotungstic acid (PTA) contrast enhanced m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
82
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(90 citation statements)
references
References 39 publications
8
82
0
Order By: Relevance
“…The temporal progression of articular cartilage score in the current study is, however, consistent with the temporal progression of structural changes in hyaline cartilage assessed in 3D by contrast enhanced micro-CT in our previous study, where significant structural changes in articular cartilage thickness where observed from 4-weeks post-surgery [29]. Our results suggest a temporal sequence of detectable structural changes in bone occurring before measurable degradation (by conventional histopathology scoring) in cartilage, but, in no way, they implicate that cell activation and macro/nano-scale tissue remodelling in the two tissues follow the same temporal order.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The temporal progression of articular cartilage score in the current study is, however, consistent with the temporal progression of structural changes in hyaline cartilage assessed in 3D by contrast enhanced micro-CT in our previous study, where significant structural changes in articular cartilage thickness where observed from 4-weeks post-surgery [29]. Our results suggest a temporal sequence of detectable structural changes in bone occurring before measurable degradation (by conventional histopathology scoring) in cartilage, but, in no way, they implicate that cell activation and macro/nano-scale tissue remodelling in the two tissues follow the same temporal order.…”
Section: Discussionsupporting
confidence: 92%
“…Using Matlab (R2011b, The MathWorks Inc., Natick, MA, USA), colour-coded maps were generated by projecting the thickness of the epiphyseal top edge onto a plane. To directly estimate the amplitude of the changes, but not for quantitative purposes (which are served by the volumetric analysis described below), profiles were computed along the medial-lateral planes in fixed-size regions (750 μm in height) that included most of the load-bearing regions and according to a methodology we previously described [29]. …”
Section: Methodsmentioning
confidence: 99%
“…Linear tetrahedral (TET4) elements are often used due to the ease and robustness of performing automatic meshing, and local and adaptive refinement with tetrahedral elements (Hubsch et al, 1995; Johnson and MacLeod, 1998; Prakash and Ethier, 2001; Spilker et al, 1992) (Delaunay, 1934; Lo, 1991a, b; Lohner, 1996; McErlain et al, 2011; Shephard and Georges, 1991; Wrazidlo et al, 1991). There are several examples in the recent literature that have used TET4 elements to discretize articular cartilage (Das Neves Borges et al, 2014; Johnson et al, 2014; McErlain et al, 2011). However, the TET4 element has several well-known numerical issues.…”
Section: Introductionmentioning
confidence: 99%
“…MicroCT reconstructions were used to visualize the formation of hard/soft tissue at the wound interface, and PTAH was used to stain the soft tissue [3436]. PTAH acts similarly to iodine in an MRI, and thus was able to distinguish the formation of either hard or soft tissue over the defected area.…”
Section: Discussionmentioning
confidence: 99%